1988
DOI: 10.1002/aic.690340702
|View full text |Cite
|
Sign up to set email alerts
|

Microdispersive interfacial mixing in fast polymerizations

Abstract: Interfacial activity between liquid reaction injection molding (RIM) reactants was observed using light microscopy. Diisocyanates were brought into contact with various diols and diamines in a thin (250 pm) gap. A dynamic phenomenon, rapidly producing a well-mixed, intermaterial phase, was discovered. It was revealed that the rate of growth of this newly formed region was dependent on both the rate of reaction and the physical properties of the initially formed product species at the reaction interface. Sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…This can be a result of a mutual increase of the equilibrium area per polar head-group when the film is in pure water and the fluctuations caused by unbinding [21,22] of the membranes when the film is in excess water. Similar [23] surface-roughening behavior has been observed when a surface-active molecule is formed by reaction at the smooth interface between two incompatible polymers. In Figure 2 a the initial evolution with time of such wrinkles was measured.…”
supporting
confidence: 69%
“…This can be a result of a mutual increase of the equilibrium area per polar head-group when the film is in pure water and the fluctuations caused by unbinding [21,22] of the membranes when the film is in excess water. Similar [23] surface-roughening behavior has been observed when a surface-active molecule is formed by reaction at the smooth interface between two incompatible polymers. In Figure 2 a the initial evolution with time of such wrinkles was measured.…”
supporting
confidence: 69%
“…This second (fast) mixing process seemed to be related to surface instabilities. Machuga et al16 confirmed the observation of other authors that the polyol at the boundary layer diffuses spontaneously and rapidly (<1 s) in the isocyanate to form a well‐mixed intermaterial phase. They found that the dimers that are formed on the boundary layer of the isocyanate and the polyol play an important role in this process.…”
Section: Theory: Reaction Kineticssupporting
confidence: 80%
“…The effect of catalyst on the interfacial process was ambivalent. Wickert et al14 observed a much finer dispersion with catalyst than without, whereas Machuga et al16 detected no difference between catalyzed and uncatalyzed experiments.…”
Section: Theory: Reaction Kineticsmentioning
confidence: 98%
“…The above rather crude analysis neglects some of the subtleties which have been recently observed, such as the microdispersive interfacial mixing, occurring within fractions of a second, upon contact at the interfacial plane of the reactants (20). This effect would further reduce the scale of segregation in actual RIM systems.…”
Section: Injection Mixingmentioning
confidence: 99%